2007
DOI: 10.1038/ncb1657
|View full text |Cite
|
Sign up to set email alerts
|

Arf6 and microtubules in adhesion-dependent trafficking of lipid rafts

Abstract: SUMMARYIntegrin-mediated adhesion regulates Rac1 membrane binding sites within lipid rafts. Detachment of cells from the substratum triggers clearance of rafts from the plasma membrane through caveolindependent internalization. The small GTPase Arf6 and microtubules also regulate Rac-dependent cell spreading and migration but the mechanisms are poorly understood. We now show that endocytosis of rafts after detachment requires F-actin, followed by microtubule-dependent trafficking to recycling endosomes (RE). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
189
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(202 citation statements)
references
References 50 publications
9
189
1
3
Order By: Relevance
“…However, replating onto fibronectin-coated substrates triggers the rapid activation of Arf6, the redistribution of internalized rafts to the plasma membrane, and a corresponding activation of Rac as the cells spread. Knockdown of Arf6 leads to the selective retention of raft components in recycling endosomes, a dramatic inhibition of adhesion-induced Rac activation, and impaired cell spreading [32]. These findings suggest that, in addition to its regulation of phospholipid-modifying enzymes and its interaction with Rac GEFs, Arf6 can further modulate Rac activity by controlling the availability of lipid raft components (Figure 3c).…”
Section: The Rac Translocation Modelmentioning
confidence: 90%
See 2 more Smart Citations
“…However, replating onto fibronectin-coated substrates triggers the rapid activation of Arf6, the redistribution of internalized rafts to the plasma membrane, and a corresponding activation of Rac as the cells spread. Knockdown of Arf6 leads to the selective retention of raft components in recycling endosomes, a dramatic inhibition of adhesion-induced Rac activation, and impaired cell spreading [32]. These findings suggest that, in addition to its regulation of phospholipid-modifying enzymes and its interaction with Rac GEFs, Arf6 can further modulate Rac activity by controlling the availability of lipid raft components (Figure 3c).…”
Section: The Rac Translocation Modelmentioning
confidence: 90%
“…Conversely, activation of endogenous Arf6 by expression of the Arf GEF ARNO (Arf nucleotide-binding site opener) was found to trigger the activation of Rac, extension of lamellipodia and the onset of migration in normally stationary epithelial cells (Figure 2) [31]. Subsequent studies have confirmed that Arf6 activation is coupled to Rac activation in several settings, including integrin ligation [32,33] or stimulation of cells with vascular endothelial growth factor (VEGF) [34], platelet-derived growth factor (PDGF) [35] or angiotensin II [36].…”
Section: Crosstalk Between Arf6 and Racmentioning
confidence: 96%
See 1 more Smart Citation
“…A major reason is that the cell/neuron may use the constitutive or stimulated ARF6 routes to control directly or indirectly the steady-state levels of cell surface receptors important for signaling, as described, for instance, for the EGF receptor (48,49), migration, or antigen presentation (50)(51)(52). Similarly, the ARF6 route likely indirectly controls APP processing by modulating BACE1 trafficking in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the effect of reggie-1 downregulation on Rac1 activation results from abnormal vesicle transport which seems to be normally governed by reggie and Rab11a. This implies that the delivery of Rac1 to specific regions in the cell occurs through its transport at vesicles in HeLa cells (Palamidessi et al, 2008).This affects the phosphoinositide composition of the transport vesicles and increases the preference of Rac1 for lipid rafts (Balasubramanian et al, 2007), which are the microdomains favored by reggies. Rac1 and Rab11 have been shown to interact genetically in Drosophila (Assaker et al, 2010).…”
Section: Influence Of Reggie On Fak Rac1 and Rab11 Activationmentioning
confidence: 99%